2020
DOI: 10.1111/tesg.12453
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transition by COVID‐19 Pandemic? The German Food Online Retail

Abstract: The COVID‐19 pandemic has led to a sharp increase in online trade. This article examines the impact of the pandemic on online grocery retail in Germany. Here we follow and refine the multi‐level perspective by Geels, and examine to what extent and why the online grocery retail expanded during the pandemic. A particular focus is on the spatial expansion into rural areas. The study shows a general upswing in the grocery trade and disproportionately high growth in online grocery trade and identifies driving and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
231
2
33

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(275 citation statements)
references
References 24 publications
9
231
2
33
Order By: Relevance
“…3 : Strategic Partnership, 4 : Environmental and Health Impacts, 5 : Obsolete Product, 6 : Reallocation Needs, 7 : Product Substitution, 8 : Destruction Costs, 9 : Defective and Returned Item. 3 : Strategic Partnership, 4 : Environmental and Health Impacts, 5 : Obsolete Product, 6 : Reallocation Needs, 7 : Product Substitution, 8 : Destruction Costs, 9 : Defective and Returned Item. 3 : Strategic Partnership, 4 : Environmental and Health Impacts, 5 : Obsolete Product, 6 : Reallocation Needs, 7 : Product Substitution, 8 : Destruction Costs, 9 : Defective and Returned Item.…”
Section: Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…3 : Strategic Partnership, 4 : Environmental and Health Impacts, 5 : Obsolete Product, 6 : Reallocation Needs, 7 : Product Substitution, 8 : Destruction Costs, 9 : Defective and Returned Item. 3 : Strategic Partnership, 4 : Environmental and Health Impacts, 5 : Obsolete Product, 6 : Reallocation Needs, 7 : Product Substitution, 8 : Destruction Costs, 9 : Defective and Returned Item. 3 : Strategic Partnership, 4 : Environmental and Health Impacts, 5 : Obsolete Product, 6 : Reallocation Needs, 7 : Product Substitution, 8 : Destruction Costs, 9 : Defective and Returned Item.…”
Section: Results Analysismentioning
confidence: 99%
“…3 : Strategic Partnership, 4 : Environmental and Health Impacts, 5 : Obsolete Product, 6 : Reallocation Needs, 7 : Product Substitution, 8 : Destruction Costs, 9 : Defective and Returned Item. 3 : Strategic Partnership, 4 : Environmental and Health Impacts, 5 : Obsolete Product, 6 : Reallocation Needs, 7 : Product Substitution, 8 : Destruction Costs, 9 : Defective and Returned Item.…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the multilevel analysis show that Internet use for daily shopping has a weaker substitution relationship with outings than other types of Internet use. Research from Germany reported that the surge in demand for online shopping has not been satis ed because of supply shortages 11 . As evidenced by the fact that living within a commercial district tended to increase going out in our multilevel analysis, online shopping alone may not have been able to meet the demand and thus did not strongly suppress going out.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focus on Internet use as a factor related to the decrease in outings. Internet use as a substitute for outings has received much attention, and it has been reported that Internet use has actually increased in various ways, including because of telework and online shopping [10][11][12][13] . However, there is little Among the purposes of Internet use, telework and online shopping have received much attention, and other purposes, such as online gaming or accessing online movies, have not been studied as much.…”
Section: Introductionmentioning
confidence: 99%